1994
DOI: 10.1111/j.1432-1033.1994.tb20004.x
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP‐Ribose) Polymerase in Plant Nuclei

Abstract: We show that poly(ADP-ribose) polymerase is present in maize, pea and wheat nuclei. We have identified the enzyme product as poly(ADP-ribose) by purification and electrophoresis on a DNA sequencing gel. This reveals a polymer ladder consisting of up to 45 residues. The polymer product from maize, after digestion with snake venom phosphodiesterase, gave only 5'-AMP and (phosphoribosy1)-AMP; the mean chain length of the polymer was 5 and 11 residues in two separate experiments. The optimum pH of the plant enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 44 publications
(30 reference statements)
2
31
0
Order By: Relevance
“…Since PARP consumes NAD + to synthesize ADP-Rib units, an examination of cellular NAD + levels can be used as an indirect measure of poly (ADP-Rib) synthesis activities (Chen et al, 1994;Du et al, 2003;De Block et al, 2005;Ishikawa et al, 2009). Whereas no significant change in NAD + levels was seen for seedlings treated with avirulent pathogen, flg22 and/or 3AB (data not shown), a statistically significant 40% to 50% decrease in NAD + compared with mock-infiltrated samples was observed in leaves 12 h after infiltration with virulent Pst DC3000 (Supplemental Fig.…”
Section: Disruption Of Parg Gene Expression Potentiates Arabidopsis Smentioning
confidence: 99%
See 2 more Smart Citations
“…Since PARP consumes NAD + to synthesize ADP-Rib units, an examination of cellular NAD + levels can be used as an indirect measure of poly (ADP-Rib) synthesis activities (Chen et al, 1994;Du et al, 2003;De Block et al, 2005;Ishikawa et al, 2009). Whereas no significant change in NAD + levels was seen for seedlings treated with avirulent pathogen, flg22 and/or 3AB (data not shown), a statistically significant 40% to 50% decrease in NAD + compared with mock-infiltrated samples was observed in leaves 12 h after infiltration with virulent Pst DC3000 (Supplemental Fig.…”
Section: Disruption Of Parg Gene Expression Potentiates Arabidopsis Smentioning
confidence: 99%
“…Use of pharmacological PARP inhibitors is a common way of overcoming such potential functional redundancy and also allows conditional inactivation of PARP activity. 3-Aminobenzamide (3AB) is a widely used PARP inhibitor in both animal (Bryant et al, 2005;Beauchamp et al, 2009;Ding et al, 2009;Hernandez et al, 2009) and plant (Phillips and Hawkins, 1985;Berglund et al, 1996;Amor et al, 1998;Tian et al, 2000;Adams-Phillips et al, 2008;Ishikawa et al, 2009) studies and has been shown to inhibit plant PARP enzymatic activity (Chen et al, 1994;Babiychuk et al, 1998). 3AB has also been used to demonstrate the linkage between PARP and PARG activity in plants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An important source of NIC release in response to stress is the DNA strand break-activated eukaryotic enzyme poly(-ADP-ribose)polymerase (PADPRP) [13,14]. PADPRP is present in nuclei of various plant species [15] and shows similarities to animal PADPRP [16]. In plants, NIC can be metabolized to N-glucose nicotinic acid or TRIG via nicotinic acid [17].…”
Section: Introductionmentioning
confidence: 99%
“…Poly(ADP-ribose) polymerase-1 (PARP-1) 1 is a multifunctional enzyme that catalyzes the formation of poly(ADP-ribose) polymers on acceptor proteins involved in the maintenance of chromatin structure and DNA repair (31)(32)(33)(34)(35)(36)(37). The addition of poly(ADP-ribose) units makes the acceptor proteins more negatively charged, thus altering their structure, function, and binding properties to DNA (38 -40).…”
mentioning
confidence: 99%